If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying H(-7) = -42 Reorder the terms for easier multiplication: -7H = -42 Solving -7H = -42 Solving for variable 'H'. Move all terms containing H to the left, all other terms to the right. Divide each side by '-7'. H = 6 Simplifying H = 6
| 2x-16=x+10 | | 0=5x-x^3 | | 12+7x=x | | 0.003(9x-3)=0.27(x+7)-1.98 | | 4x-26=2x+18 | | (13b-6)-4(3b+1)=-7 | | 6/7c=18 | | 3x+6(2x-3)=4+7x | | -10-4x+(-4)=70 | | -12r=-5 | | 2(2-4)=3(z-4) | | 3w^3/4w*9/w | | 3/4c=12 | | 5x+6x+3+8=8x+5+2x | | 7x^2-400=0 | | x/5=3y+7 | | 2377960+26T=2067959+125T | | 10x^2+8.5X+5=0 | | 10Y=40 | | x+[x-4]+4[x-4]=52 | | -4+12t=100 | | 3x+2=-4x+23 | | y+2x=-3x+1 | | 9p+2=9+8p | | 2(2y-4)=12x | | 2(2y-4)=12x | | 2e-3.1=1.7 | | y=3x^3-3x^2 | | y-11=7 | | 2377960+26T=3000000 | | 7x+9y+17z=19y+13x+4z | | =24x^2-48x+16 |